ANALISIS KARAKTER SISWA KELAS IV SEKOLAH DASAR MELALUI INTERAKSI TEMAN SEBAYA DI SDN 101/VIII RANTAU API - Khotimah; Idris, Ilyas; Saputra, Donal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Peer groups constitute one of the most influential social environments in shaping the character of elementary school students. Intensive interactions among peers may produce both positive and negative effects on students' character development. This study aimed to analyze the role of peer groups in shaping the character of fourth-grade students at SD Negeri 101/VIII Rantau Api, describe their characteristics, and identify the positive and negative impacts of peer interactions on character formation. This study employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation, and analyzed using the interactive model of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation. The findings revealed that peers function as behavioral models, sources of social learning, providers of social support, social controllers, identity builders, motivators, and scaffolding in the learning process. These interactions contributed to the development of discipline, cooperation, social care, responsibility, empathy, and self-confidence. However, peer influence may also lead to undesirable behaviors, including indiscipline, imitation of negative behaviors, and decreased learning concentration when students are exposed to less supportive peer environments. This study highlights that the quality of peer relationships plays a crucial role in character formation. Therefore, collaboration among schools, teachers, and parents is essential to create a positive social environment that supports students' character development.